Clinico-epidemiological and hematological profile of anemia in preschool children (12 months to 60 months) A hospital-based prospective observational study - Agarwal, Tanay; Parasher, Vivek; Goyal, Suresh Chandra; Khatri, Rahul; Satija, Vaishali (Journal of Neonatal Surgery, 2025)
Introduction: Anemia, a major public health concern, affects nearly 39.8% of preschool children globally, with the highest burden in South Asia and Africa. In India, NFHS-5 (2019–21) reported anemia in 67.1% of children under five, with Rajasthan exhibiting an alarming prevalence of 71.5%. Iron deficiency remains the leading cause, though vitamin B12, folate deficiencies, and chronic infections also contribute. Anemia in early childhood is linked to cognitive impairment, developmental delays, and increased morbidity, emphasizing the need for targeted interventions. Materials and Methods: A hospital-based prospective study was conducted in the Department of Pediatrics, Pacific Institute of Medical Sciences, Udaipur, from May 2023 to April 2024. The study included 196 anemic children aged 12–60 months. Demographic, clinical, and hematological data were collected using a structured proforma. Hematological parameters were analyzed using an automated hematology analyzer, peripheral blood smear, and biochemical assays for iron and vitamin B12 levels. Statistical analysis was performed using SPSS v28, with p<0.05 considered significant. Results: The study found a higher prevalence of anemia in rural children (65.8%) and lower socioeconomic groups (53.6%). Microcytic hypochromic anemia (64.3%) was the most common type, with iron deficiency (47.3% vs. 31.0%, p=0.003) predominant in younger children, while older children had higher rates of sickle cell (p=0.042) and aplastic anemia (p=0.016). Younger children had lower mean hemoglobin (8.1 vs. 9.4 g/dL, p<0.001) and MCV (72.6 vs. 78.3 fL). Clinical findings included pallor (87.8%), fever (57.1%), and weakness (68.9%). Conclusion: Anemia remains a significant burden among preschool children, primarily due to iron deficiency. Socioeconomic and rural-urban disparities highlight the need for targeted nutritional interventions and routine screening programs. Strengthening parental education, dietary supplementation, and preventive strategies could help mitigate anemia ’s long-term impact. Future community-based studies are needed to validate findings and evaluate intervention outcomes.